2004
DOI: 10.1038/sj.bjp.0705601
|View full text |Cite
|
Sign up to set email alerts
|

The endothelin system in Morris hepatoma‐7777: an endothelin receptor antagonist inhibits growth in vitro and in vivo

Abstract: 1 Plasma concentrations of endothelin are increased in patients with hepatocellular cancer as well as in patients with liver metastasis. However, the impact of these findings remains uncertain. 2 We thus analyzed the endothelin system in a rat hepatoma model (Morris hepatoma 7777) in vitro and in vivo. 3 Our study revealed that tissue concentrations of endothelin-1 (ET-1) and big-ET-1, the precursor of ET-1, were significantly elevated in Morris hepatoma 7777 as compared to normal liver. The ETA receptor densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…We found the alanine to total carbon ratio is significantly higher in HCC tumors than in normal livers. This may be related to the reported high ALT level in the Morris HCC rat model (35,36). Even though the same amount of hyperpolarized 13 C-pyruvate solution was injected in each animal, the up-take of 13 C-pyruvate by each HCC tumor varies, as indicated by the wide range of total carbon signal found in HCC tumors (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We found the alanine to total carbon ratio is significantly higher in HCC tumors than in normal livers. This may be related to the reported high ALT level in the Morris HCC rat model (35,36). Even though the same amount of hyperpolarized 13 C-pyruvate solution was injected in each animal, the up-take of 13 C-pyruvate by each HCC tumor varies, as indicated by the wide range of total carbon signal found in HCC tumors (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, we hypothesized that the 13 C-lactate signal relative to the injected 13 C-pyruvate, which was quantified as the total 13 C signal (or total carbon) in this work, may not differentiate HCC tumor and normal liver. However, in some liver diseases, including hepatoma (35,36), the enzyme catalyzing pyruvate conversion to alanine, Alanine Transaminase (ALT), is elevated and we postulated a potential difference in 13 C-alanine. In this study, hyperpolarized 13 C-pyruvate was injected into both normal and HCC rats to measure both the signal levels and T 2 's of 13 C-lactate and 13 C-alanine.…”
Section: Introductionmentioning
confidence: 99%
“…Endothelin 1 (EDN1) is a 21-amino acid peptide that exerts a wide range of biological activities. It is recognized as a vasoconstrictor peptide and has been implicated in the growth regulation of several tumors [12] , [13] . EDN1 has been found to enhance tumor growth by promoting angiogenesis [14] , [15] .…”
Section: Introductionmentioning
confidence: 99%
“…EDN1 secretion in hepatoma cells has been described [26] , [27] . Hepatoma cell growth increases upon the exogenous addition of EDN1 in a dose-dependent manner [12] . The tissue concentrations of EDN1, big ET-1, and the ETA receptor were significantly increased in hepatoma tissue compared to normal liver tissue [12] .…”
Section: Introductionmentioning
confidence: 99%
“…ET-1 secretion in HCC is stimulated by various cytokines and growth factors (13). Elevated levels of ET-1 have been observed in HCC tissues compared with corresponding normal liver tissues (14). It has previously been demonstrated that ET-1 upregulation increases HCC cell proliferation, invasion and migration, and inhibits apoptosis (15).…”
Section: Introductionmentioning
confidence: 99%